Los derechos en broma. Análisis, comentarios y críticas - Merayo Fernández, Rodrigo (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
Los derechos en broma is a provocative, audacious, combative and innovative book in terms of the questions and the issues which it addresses. For this reason, in this book, Pablo de Lora rescues a ’’traditional’’ or ’’classical’’ perspective of rights and legislation that, he argues, should inspire contemporary democratic legal systems in the face of what he considers a ’’moralisation’’ of politics (and, therefore, of law) in the context of liberal democracies. Through five chapters and an epilogue, some issues of particular significance and worthy of debate in and for the quality and effectiveness of our democracies are brought to the discussion. In this analysis and commentary on Los derechos en broma, an attempt is made to give an account of the points that have been considered most relevant for philosophical, political and legal discussion and dialogue, as well as outlining some criticisms of some of these and the foundations or arguments that accompany them.